2012
DOI: 10.1021/nl301318b
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Modeling Reveals Poisoning Mechanisms of MgO-Supported Au Clusters in CO Oxidation

Abstract: Catalyst deactivation mechanisms on MgO-supported Au(6) clusters are studied for the CO oxidation reaction via first-principle kinetic Monte Carlo simulations and shown to depend on support vacancies. In defect-poor MgO or in the presence of a Mg vacancy, O(2) does not bind to the clusters and the catalyst is poisoned by CO. On Au clusters interacting with O vacancies of the support, O(2) can be chemisorbed and transient activity is observed. In this case, an unexpected catalyst "breathing" mechanism (restruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
85
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(87 citation statements)
references
References 54 publications
1
85
0
Order By: Relevance
“…For a general overview of KMC approaches and applications in heterogeneous catalysis the reader is referred to Ref. 55. Here, we will briefly review the framework and present in detail the calculation of the energetics which is the focus of the present work.…”
Section: Methodsmentioning
confidence: 99%
“…For a general overview of KMC approaches and applications in heterogeneous catalysis the reader is referred to Ref. 55. Here, we will briefly review the framework and present in detail the calculation of the energetics which is the focus of the present work.…”
Section: Methodsmentioning
confidence: 99%
“…22 The accumulation or depletion of electron density at a metal active sitethe atomic chargecan significantly alter adsorbate binding strength and, as a result, reactivity. 21,44 To analyze the effects of catalyst−support interactions on charge transfer, we used Bader charge analysis. 45,46 Here, we are interested in trends and not specific values of the charges, which can be very different, depending on the method used to The Journal of Physical Chemistry C Article estimate charges.…”
Section: ■ Introductionmentioning
confidence: 99%
“…17,24 One of the simplest and the most studied catalytic reaction on gold clusters is a low-temperature CO oxidation by molecular oxygen. 1,2,10,12,17,[24][25][26][27][28][29][30][31] It has been demonstrated that dispersed gold supported on Co 3 O 4 , NiO, TiO 2 , and Fe 2 O 3 possesses high catalytic activity for CO oxidation. [32][33][34][35] These supports affect dramatically the catalytic activity of gold clusters.…”
Section: Introductionmentioning
confidence: 99%